EXTH-71. FUNCTIONAL GENOMICS IDENTIFIES EPIGENETIC REGULATORS AS NOVEL THERAPEUTIC TARGETS FOR SONIC HEDGEHOG MEDULLOBLASTOMA. (12th November 2021) - Tsiami, Foteini; Piccioni, Federica; Root, David; Bandopadhayay, Pratiti; Segal, Rosalind; Tabatabai, Ghazaleh; Merk, Daniel
Abstract: Medulloblastoma (MB) is among the most common malignant pediatric brain tumors. Among its four molecularly heterogeneous clinical variants, sonic hedgehog (SHH) subgroup comprises 30% of all MBs and is characterized by constitutive activation of the canonical SHH signaling pathway. Although Smoothened ( Smo ) inhibition has emerged as a promising therapeutic target for this tumor entity, primary or acquired resistance impedes its clinical efficacy. Thus, further insight into the molecular mechanisms underlying acquired resistance to Smo inhibition are urgently needed to overcome this challenge. Here, we performed a genome-wide CRISPR/Cas9 knockout screen in a murine and a human SHH-MB cell line, SMB21 and DAOY, respectively, in order to unravel tumor-specific genetic vulnerabilities. Our data provide functional evidence that SMB21 cells highly depend on key members of the SHH pathway such as Smo and Gli1 for their survival. In contrast, none of those positive regulators of SHH signaling scored in DAOY cells, suggesting that they are not a faithful human model of this tumor subtype. Of note, functional genomics identified SMB21-context specific essentialities beyond the SHH pathway that include epigenetic regulators such as Dnmt1, Smarca5 and Smarca4 . Further in vitro pharmacological validations demonstrate that Dnmt1 inhibition is efficacious in clinically relevant concentrations in SHH-associated cell lines, both sensitive and resistant to Smo inhibition, suggesting novel therapeutic avenues for SHH-MB. By employing genome-scale knockout screens in murine cell lines faithfully recapitulating the biology of human SHH-MB, we aim to decipher synthetic lethal interactors for Dnmt1 inhibitors that could potentially serve as a combinatorial treatment approach for SHH-MB. Finally, genetic ablation and pharmacological inhibition of epigenetic regulators will be evaluated in in vivo mouse models of SHH-MB. Summarizing, our data highlight the potential of inhibitors of epigenetic regulators in SHH-MB sensitive, as well as resistant to Smo inhibition.